2016
DOI: 10.1111/irv.12388
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices about influenza illness and vaccination: a cross‐sectional survey in two South African communities

Abstract: BackgroundUnderstanding knowledge and sentiment toward influenza and vaccination is important for effective health messages and prevention strategies. We aimed to characterize knowledge, attitudes, and practices surrounding influenza illness and vaccination in two South African communities and explore reasons for vaccine hesitancy.MethodsHousehold primary caregivers in Soweto and Klerksdorp townships were interviewed about knowledge of influenza and intention to receive an influenza vaccine using a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…Cultural norms may have been influential in the decision to attend these gatherings despite the health risks, especially among the older generation. Previous research has also shown that those with higher income were less willing to comply with health recommendations [21] perceived less fear and more control in pandemic situations [22].…”
Section: Plos Onementioning
confidence: 97%
“…Cultural norms may have been influential in the decision to attend these gatherings despite the health risks, especially among the older generation. Previous research has also shown that those with higher income were less willing to comply with health recommendations [21] perceived less fear and more control in pandemic situations [22].…”
Section: Plos Onementioning
confidence: 97%
“…However, emotions experienced at the point of decision-making may be as important in health behaviour as a cognitive assessment of the risk, such as worry and anticipated regret, which have also been shown to be predictive of influenza vaccination [20] , [25] , [26] . Few studies have used the HBM to study influenza vaccine behaviour in LMICs [27] , [28] , [29] , [30] , [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Participants often defined influenza as a condition characterized by nasal congestion or difficulty breathing, consistent with findings from South Africa [17,19]. Overlap in symptoms with other conditions meant some people saw influenza as a symptom or cause of conditions such as malaria and pneumonia.…”
Section: Discussionmentioning
confidence: 62%
“…There is considerable research on public perceptions of influenza in high-income countries [12,15,16], and growing research in middle-income countries. For example, research in South Africa, Kenya and India found varied understandings of influenza, including knowledge of viruses and contagion but also explanations that differed from biomedical models, such as influenza being caused by dust, weather and dirt [1719]. Little is known about perceptions and behaviours about influenza in low-income countries [20].…”
Section: Introductionmentioning
confidence: 99%